2013
DOI: 10.1016/j.mam.2012.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of mammalian Rh glycoproteins (SLC42 transporters) and their role in acid–base transport

Abstract: The mammalian Rh glycoproteins belong to the solute transporter family SLC42 and include RhAG, present in red blood cells, and two non-erythroid members RhBG and RhCG that are expressed in various tissues, including kidney, liver, skin and the GI tract. The Rh proteins in the red blood cell form an “Rh complex” made up of one D-subunit, one CE-subunit and two RhAG subunits. The Rh complex has a well-known antigenic effect but also contributes to the stability of the red cell membrane. RhBG and RhCG are related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 67 publications
1
25
0
Order By: Relevance
“…Expression of Rhag-like mRNA was found in the erythrocytes and spleen, while Rhcg-like mRNA expression was detected in the gill. This tissue distribution pattern supports the classification of Rh mRNAs (83,85,128). In situ hybridization using adjacent sections demonstrated that the mRNAs of GS, OTC, and Rhp2 were colocalized in the same nephron segment of the proximal tubule (Fig.…”
Section: Urea Synthesis In the Kidneysupporting
confidence: 82%
“…Expression of Rhag-like mRNA was found in the erythrocytes and spleen, while Rhcg-like mRNA expression was detected in the gill. This tissue distribution pattern supports the classification of Rh mRNAs (83,85,128). In situ hybridization using adjacent sections demonstrated that the mRNAs of GS, OTC, and Rhp2 were colocalized in the same nephron segment of the proximal tubule (Fig.…”
Section: Urea Synthesis In the Kidneysupporting
confidence: 82%
“…These observations suggest that increased Rhbg expression is not likely to be contributing to the decrease in ammonia excretion. Rhbg has also been suggested to function as a CO 2 transporter (16,42), but because intercalated cell CO 2 transport is necessary for intracellular H ϩ generation used for urinary acidification, and dietary protein restriction causes urine alkalinization, this function is unlikely to underlie its increased expression during dietary protein restriction. Importantly, collecting duct Rhbg expression does not appear to be necessary for the changes in renal ammonia excretion in response to dietary protein restriction.…”
Section: Discussionmentioning
confidence: 99%
“…These were only identified as NH 3 /NH 4 1 transporters in recent years (75,76). These proteins function as NH 3 /NH 4 1 transporters, clearly facilitating diffusion of NH 3 but also, probably including (at least for RhBG) electrogenic transport of NH 4 1 (77,78). RhBG is present in the basolateral membrane of type A ICs and can transport NH 4 1 and NH 3 into the cell, whereas RhCG, present at the apical membrane of several cell types (and in some circumstances, basolateral membrane), transports NH 3 into the lumen.…”
Section: Nhmentioning
confidence: 99%